MENINGKATKAN HASIL BELAJAR BIOLOGI PADA MATERI SISTEM EKSKRESI MELALUI PENERAPAN MODEL RESOURCE BASED LEARNING PADA SISWA KELAS VIII SMP NEGERI 40 MAKASSAR - Gaudensia P. Luhur; Rezeki Amaliah (Cross-border, 2021)
This research is a classroom action research which aims to improve student learning outcomes in class VIII4 SMPN 40 Makassar, through the application of the Resource Based Learning model. The research subjects were 32 students consisting of 15 males and 17 females. The first Cycle was held in 2 meetings, data collection was carried out using learning outcomes tests and then the data obtained were analyzed descriptively qualitatively and quantitatively. The results obtained are as follows: (1) Biology learning outcomes of class VIII4 students of SMPN 40 Makassar in the first cycle are in the complete category as many as 21 people, and 11 students incomplete. With an average score of 69.84 out of 32 people with the highest score of 80 and the lowest score of 50. (2) Biology learning outcomes of class VIII4 students of SMPN 40 Makassar in the second cycle were in the complete category of 32 people or in other words all completed. With an average score of 81.93 out of 32 people, the highest score was 95 and the lowest was 70. (3) There was an increase in biology learning outcomes in class VIII4 students of SMPN 40 Makassar from cycle I to cycle II. The results of the study concluded that the resource based learning model could improve biology learning outcomes in class VIII4 students of SMPN 40 Makassar.